Study the effect of crude oil and nanoenterosorbent "Ingo-2" on hematological parameters of blood in rats (Experimental biology, 2015)
The article presents the results of investigation of the influence of crude oil and enterosorbents on hematological parameters of blood in test animals. It was found that crude oil is the non-specific response of the body to the contamination of small mammals , which stress factor for animals. It is shown that the use of a chelator in the purifier body from toxicity of oil greatly reduces the adverse impact on the homeostasis of oil .
Keywords: pollution; crude oil; chronic intoxication; nanoenterosorbent; rats; hematological parameters of blood